ORIENTASI PENGEMBANGAN KURIKULUM SEKOLAH DASAR DALAM PERSPEKTIF KURIKULUM MILLER DAN SELLER - Agustinus Tanggu Daga (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aims to describe the theoretical perspective of Miller and Seller on curriculum development at primary schools. The literature study method was applied to collect the data from relevant resources. This research finds that Miller and Keller’s curriculum orientation involves transmission, transaction, and transformation. The curriculum development for primary schools in the transmission orientation emphasizes the transfer of knowledge, skills, and values to students through learning subjects. Its learning process focuses on teachers while its learning strategy is expository and its learning evaluation utilizes traditional test instruments. The emphasis of transaction orientation is the interaction between curriculum and students. The teacher plays the role of facilitator to assist students in constructing knowledge. The learning strategy used is a scientific approach with active, collaborative, and inquiry learning methods. Then, the learning evaluation uses authentic assessment. Whereas, the curriculum development in the transformation orientation emphasizes the students’ personal and social transformation in which its learning strategy is implemented to encourage students to find the meaning and value of learning processes as well as to apply them in the real life. The teacher plays a role as a motivator and learning facilitator and its learning evaluation is based on the authentic assessment by emphasizing performance and behaviour appraisal of primary school students.  Finally, this research concludes that the primary school curriculum in transmission orientation is an academic subject curriculum that emphasizes an integrated curriculum organization. The primary school curriculum in transaction orientation is designed for solving social problems by using the scientific paradigm. The primary school curriculum in transformation orientation is designed in order that students are able to carry out personal and social transformation holistically.